Gender Specific Re-organization of Resting-State Networks in Older Age - Goldstone, Aimée; Mayhew, Stephen D.; Przezdzik, Izabela; Wilson, Rebecca S.; Hale, Joanne R.; Bagshaw, Andrew P. (Frontiers in Aging Neuroscience, 2016)
Advancing age is commonly associated with changes in both brain structure and function. Recently, the suggestion that alterations in brain connectivity may drive disruption in cognitive abilities with age has been investigated. However, the interaction between the effects of age and gender on the reorganisation of resting-state networks is not fully understood. This study sought to investigate the effect of both age and gender on intra- and inter-network functional connectivity (FC) and the extent to which RSN node definition may alter with older age. We obtained resting-state functional magnetic resonance images from younger (n=20) and older (n=20) adults and assessed the FC of three main cortical networks: default mode (DMN), dorsal attention (DAN) and saliency (SN). Older adults exhibited reduced DMN intra-network FC and increased inter-network FC between the anterior cingulate cortex (ACC) and nodes of the DAN, in comparison to younger participants. Furthermore, this increase in ACC-DAN inter-network FC with age was driven largely by male participants. However, further analyses suggested that the spatial location of ACC, bilateral anterior insula and orbitofrontal cortex RSN nodes changed with older age and that age-related gender differences in FC may reflect spatial re-organisation rather than increases or decreases in FC strength alone. These differences in both the FC and spatial distribution of RSNs between younger and older adults provide evidence of reorganisation of fundamental brain networks with age, which is modulated by gender. These results highlight the need to further investigate changes in both intra- and inter- network FC with age, whilst also exploring the modifying effect of gender. They also emphasise the difficulties in directly comparing the FC of RSN nodes between groups and suggest that caution should be taken when using the same RSN node definitions for different age or patient groups to investigate FC.